The Technological Pedagogical Content Knowledge (TPACK) Competence of Vocational High School Teacher - Johar Maknun (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
This study aimed to determine the Technological Pedagogical Content Knowledge (TPACK) competence of Vocational High School teachers. A descriptive method was implemented through a survey. This study location was 3 Vocational High Schools in Bandung City, West Java Province, Indonesia. Furthermore, the participants were 90 teachers. The TPACK competency evaluation instrument for Vocational High School teachers was based on its components, namely Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), and Technological Pedagogical Content Knowledge (TPACK). The results of this study showed the TPACK competence of the Vocational High School teachers was 3.68 which was classified as high. The maximum and minimum score was 3.84 and 3.58 for the Content Knowledge and Technological Knowledge component, respectively. This indicates that the teachers had the highest competence in knowledge of subject matter content and the lowest in understanding and applying technology to learning. Therefore, there was still a need for efforts to improve the competence of these teachers in understanding and applying technology in learning.